Body mass index among secondary school students in Nineveh Governorate - Al Murad, Zainy; Sulaiman, Hashim; Muhamad, Nuhaa (Journal of Physical Education, 2023)
The research is summarized by finding the body mass index of secondary school students in the center of Nineveh Governorate from the first to the sixth grade, which is extracted through measurements of height and weight. The BMI is a mathematical value that is extracted from dividing the weight in kilograms by the square of the height in meters. It is for adults. Curves have been developed for children up to 18 years of age. BMI helps to calculate the fat mass index, which expresses obesity. The research aims to identify the curves of the body mass index in the research sample and to identify the descriptive picture of this indicator, which gives those in charge of the educational and health process helps them in preparing curricula and treatments that guarantee the health status of the students. The two age groups are (12-15) years and (16-18) years.The arithmetic means, standard deviations, the law (t) of differences, and analysis of variance were used, and the results showed the presence of significant differences in favor of the higher age group in the obesity index, while between classes the differences were significant and not significant.